25-O-acetyl-23, 24-dihydro-cucurbitacin F induces cell cycle G2/M arrest and apoptosis in human soft tissue sarcoma cells. (22nd April 2015) - Lohberger, Birgit; Kretschmer, Nadine; Bernhart, Eva; Rinner, Beate; Stuendl, Nicole; Kaltenegger, Heike; Kahl, Stefan; Bauer, Rudolf; Leithner, Andreas
Abstract: Ethnopharmacological relevance: Quisqualis indica is used in traditional Chinese medicine to treat cancer and related syndromes and also known for its anthelminthic effects. Aim of the study: Soft tissue sarcomas represent a rare group of malignant tumors that frequently exhibit chemotherapeutic resistance and increased metastatic potential. In this study, we evaluated the cytotoxic, apoptosis inducing and cell cycle arresting effects of 25-O-acetyl-23, 24-dihydro-cucurbitacin F which has been isolated from leaves and twigs of Q. indica . Material and methods: The present study investigates the effects of 25-O-acetyl-23, 24-dihydro-cucurbitacin F (1 ) on cell viability, cell cycle distribution, and apoptotic induction of three human sarcoma cell lines of various origins by using the CellTiter 96 ® AQueous One Solution Cell Proliferation Assay, flow cytometrical experiments, real-time RT-PCR, Western blotting, and the Caspase-Glo ® 3/7 Assay Results: We could show that1 reduced cell viability in a dose-dependent manner and arrested the cells at the G2/M interface. The accumulation of cells at the G2/M phase resulted in a significant decrease of the cell cycle checkpoint regulators cyclin B1, cyclin A, CDK1, and CDK2. Interestingly, 1 inhibited survivin expression significantly, which functions as a key regulator of mitosis and programmed cell death, and is overexpressed in many tumor types including sarcomas. Moreover, 1 induced apoptosis in liposarcoma and rhabdomyosarcoma cells caspase-3 dependently. Conclusion: Our data strongly support1 as a very interesting target for further investigation and development of novel therapeutics in sarcoma research. Graphical abstract: